Structural Balance and Fiscal Policy in Peru: 1990-2002 - Ormeño S., Arturo (2014)
This document presents a methodology for the calculation of the Structural Balance of the Public Sector and its application to the Peruvian economy during the period 1990-2002. There are two objectives for this research effort. First, it permits the evaluation of the economic authority's behavior during the period under analysis. Second, it allows the specification of a rule for fiscal policy. This rule is embedded into a general equilibrium model.The results obtained show that the Central Government management of its accounts can be characterized as pro-cyclical between 1990 and 1997 and counter-cyclical for the period 1996-2001. However, the results for the second and third quarter of 2002 show preliminary evidence of a change in fiscal policy towards a pro-cyclical pattern.Finally, and as expected, the incorporation of a fiscal rule into the general equilibrium model results in changes in the evolution of the fiscal deficit and the public debt stock. Both accounts fall more sharply in the occurrence of a positive terms of trade shock when the rule is added to the model than when it is not. Other results associated to the incorporation of the fiscal rule are: (i) a decline in the rate of growth of public expenditures due to the reduction in interest payments; (ii) a reduction in the rate of growth of imports; and (iii) an increase in the net foreign asset position of the economy.